1996
DOI: 10.1136/jmg.33.5.409
|View full text |Cite
|
Sign up to set email alerts
|

Renal-hepatic-pancreatic dysplasia: an autosomal recessive malformation.

Abstract: We report two brothers with a cystic malformation of the kidneys, liver, and pancreas. In both cases the malformation was fatal and the children died shortly after birth. The pathological findings, consisting of multicystic dysplastic kidneys, dilated and dysgenetic bile ducts, dilated pancreatic ducts, and polysplenia, correspond to those reported by Ivemark as renal-hepatic-pancreatic dysplasia. Many polymalformation syndromes include cystic affectation of these three organs, so this syndrome could be an iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Other complex syndromes [Adès et al, 1994] can combine several findings of Cumming syndrome. Thus, Ivemark et al [1959] and others [Bernstein et al, 1987, Neuhaus et al, 1996, Torra et al, 1996 described a combination of renal, pancreatic, and liver dysplasia with autosomal recessive inheritance. Involvement of other organs, and the lack of campomelia and external malformations of Cumming syndrome, can exclude the renal-hepatic-pancreatic dysplasia syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Other complex syndromes [Adès et al, 1994] can combine several findings of Cumming syndrome. Thus, Ivemark et al [1959] and others [Bernstein et al, 1987, Neuhaus et al, 1996, Torra et al, 1996 described a combination of renal, pancreatic, and liver dysplasia with autosomal recessive inheritance. Involvement of other organs, and the lack of campomelia and external malformations of Cumming syndrome, can exclude the renal-hepatic-pancreatic dysplasia syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologically, the latter cases may be difficult to differentiate from extrahepatic biliary obstruction with ascending infection, particularly since there may be an associated tissue cholestasis. The correct diagnosis must be based on the history, clinical findings and • Asplenia with cystic liver, kidney and pancreas, which represents Ivemark syndrome with variants, 549 possibly in the same spectrum as renal-hepatic-pancreatic dysplasia • Ellis-van Creveld syndrome or chondroectodermal dysplasia 550 with polydactyly, short limbs, short ribs, postaxial polydactyly, and dysplastic nails and feet, which has been mapped to chromosome 4p16…”
Section: Juvenile and Adult Presentation -Congenital Hepatic Fibrosismentioning
confidence: 99%
“…Both Hirschsprung disease [Mishalany et al, 1982] and neural tube defects [Van Went et al, 1977] have been associated with lateralization disorders. Torra et al, [1996] reported an association between polysplenia and multicystic dysplastic kidneys.…”
Section: Discussionmentioning
confidence: 99%